2014
DOI: 10.1002/srin.201300302
|View full text |Cite
|
Sign up to set email alerts
|

Calculation Model of Using Appropriate High Reactivity Coke in Blast Furnace

Abstract: The technology of using high reactivity coke in iron‐making process by blast furnace has been verified to promote the reduction of iron ore in the thermal reserve zone through theoretical analysis combined with experimental research. However, the absence of relative calculation model makes it difficult to determine the coke saving ability quantitatively and supply substantial guidance for industry. In present study, thermal reserve zone and high temperature zone are taken as investigation objects and a calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, relevant theoretical research and production practice have demonstrated that it is feasible to use high-reactivity coke for hydrogen-rich blast furnaces. 18 22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, relevant theoretical research and production practice have demonstrated that it is feasible to use high-reactivity coke for hydrogen-rich blast furnaces. 18 22 …”
Section: Introductionmentioning
confidence: 99%
“…Low-reactivity coke is widely used as the main reducing agent for blast furnace ironmaking in the steel industry. However, relevant theoretical research and production practice have demonstrated that it is feasible to use high-reactivity coke for hydrogen-rich blast furnaces. …”
Section: Introductionmentioning
confidence: 99%
“…As for exp-CSR, the spraying method showed obvious advantages when the concentration of H 3 BO 3 exceeded 1.0 wt%. Previous research 36) shows the 1 kg coke can be saved per ton iron when the CRI is reduced by 1%. The CSR is improved which strengthens the skeleton function of coke in the BF.…”
Section: Structure Of Metallurgical Coke Before and Aftermentioning
confidence: 97%
“…Low reactivity of coke is generally desired by the blast furnace operators, although scientific research interest has also been shown toward the use of highly reactive coke, [3,[37][38][39][40][41] which when properly utilized could decrease the temperature of the thermal reserve zone, as well as lowering the reducing agent rate and CO 2 emissions.…”
Section: A Chemical Reactivity Of Coke In Four Different Gas Profilesmentioning
confidence: 98%